Genetic and Environmental Contributions to Long-Term Sick Leave and Disability Pension: A Population-Based Study of Young Adult Norwegian Twins. (7th June 2013) - Gjerde, Line C.; Knudsen, Gun Peggy; Czajkowski, Nikolai; Gillespie, Nathan; Aggen, Steven H.; Røysamb, Espen; Reichborn-Kjennerud, Ted; Tambs, Kristian; Kendler, Kenneth S.; Ørstavik, Ragnhild E.
Abstract : Although exclusion from the workforce due to long-term sick leave (LTSL) and disability pension (DP) is a major problem in many Western countries, the etiology of LTSL and DP is not well understood. These phenomena have a strong association as most patients receiving DP have first been on LTSL. However, only a few of those on LTSL end up with DP. The present study aimed to investigate the common and specific genetic and environmental risk factors for LTSL and DP. The present study utilizes a population-based sample of 7, 710 young adult twins from the Norwegian Institute of Public Health Twin Panel, which has been linked to the Historical-Event Database (FD-Trygd; 1998–2008). Univariate and bivariate twin models were fitted to determine to what degree genetic and environmental factors contribute to variation in LTSL and DP. The estimated heritabilities of LTSL and DP were 0.49 and 0.66, respectively. There was no evidence for shared environmental or sex-specific factors. The phenotypic-, genetic-, and non-familial environmental correlations between the variables were 0.86, 0.82, and 0.94, respectively. Our results indicate that familial transmission of LTSL and DP is due to genetic and not environmental factors. The risk factors contributing to LTSL and DP were mainly shared, suggesting that what increases risk for LTSL also increases risk for DP. However, a non-negligible part of the genetic variance was not shared between the variables, which may contribute to explaining why some progress from LTSL to DP, whereas others return to work.